Professor empreendedor competências para uma educação significativa - Melo, Cleide Oliveira Silva (2018)
The purpose of this research was to study faculty actions in teachers' pedagogical work, seeking to identify the entrepreneurial attitude that leads these professionals to adapt themselves to a context of demands of a globalized and technological society, which imposes new forms of work organization. From this perspective, we discuss what is to entrepreneur in education, analyze the dimensions of teaching practice, the constitution of the teachers' knowledge and their professional development, trying to understand if entrepreneur is a constituent part of the faculty, which allows them to innovate in classroom, adding new informational technologies in the quest for meaningful and contextualized education for their students. In order to carry out this research, we opted for a qualitative descriptive approach, since we understand that this method is the most appropriate for the comprehension, analysis and description of the phenomenon. As for the research instrument, we selected the semistructured interview as a means to favor the description of social phenomena, their explanation and understanding. The research universe corresponded to university teachers who work in the e-learing, in a sample of eight teachers, as we believe that e-learing, based on digital technologies, demands even more innovative capacities and creativity from teachers, that is, entrepreneur to achieve efficiency and quality. The relevance of the research is to raise discussions about an subject poorly studied in the faculty, the entrepreneurial dimension, important for this professional to meet the current demands in business and society. The results of this research indicated that more than ever, entrepreneur has to be part of the dimension of the teaching action and its knowledges, and this capacity must be stimulated as a presupposition of the professional development of teachers, in face of the new demands of the society, that requests the formation of more proactive individuals, who have an attitude and are responsible for building their knowledge path, aiming at their personal and professional life project.